Wzmacnianie motywacji do zmiany zachowań dysfunkcyjnych u patologicznych hazardzistów osadzonych w jednostkach penitencjarnych - Piasecka, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In recent years, more and more attention has been paid to behavioural addictions, which result from an increase in the number of people who experience diﬃculties within this area. Imprisoned pathological gamblers constitute a speciﬁc group in psychotherapy. The following paper presents a review of the literature within the scope of aid actions directed at this group of people.
Keywords: hazard patologiczny; uzależnienie; terapia; zakłady karne